SOA Governance Best Practices- Architectural, Organizational, and SDLC Implications taking the management of services to the next level. - Carlson, Brent (SOA webservices journal.)
The fact that you're reading this article means that you are probably plannning a service-oriented architecture (SOA) initiative and recognize that some level of governance is required in order to be successful. If you are like most people in this position, you are also somewhat confused as to the meaning of SOA governance. Governance is the current buzzword and combining governance with SOA creates a phrase that every independent software vendor (ISV) wants a piece of. How do you sort out what is marketing hype from what is truly valuable and relevant to your organization's SOA efforts?